STRATEGI PENETAPAN HARGA PADA BISNIS JASA VIDEO STAGGER MEDIA - Prayogo, Henry (PERFORMA, 2017)
The purpose of this study is to set up the accurate pricing strategy in video service business Stagger Media. This research used the calculation of cost plus (mark up) pricing, value based pricing & competitive based pricing and also analysis to loss leading pricing method. This research used descriptive qualitative research which uses the company’s data to obtain information. Observation, interview, and documentation are used as a data collection methods in this research, while source triangulation is used as data analysis tool. Based on the predetermined set of criteria, four study informants are selected. They are the owner of Dynamic Motion, the owner of Attipatra, expert video Samuel tirta and expert video Daniel Christian. Based on the data analysis on calculation in each every pricing methods, Stagger Media choose cost plus (mark up) pricing as a pricing strategy to its company.